Letter from Carl D. Duncan to Patricia Whiting, July 25, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan states that he is looking forward to spending time with Whiting going to dinner, having a relaxation session, and taking a trip to Washington, D.C.